Rate and Causes of 30-day Unplanned Readmission/Return Following Head and Neck Surgery at a Tertiary Care Center in Saudi Arabia - Mazin Merdad; Abdulsalam Alqutub; Ahmed Mogharbel; Abdullah A. Alghamdi; Omar Alsulami; Mohammed Awadh; Ahmed S. Alsulami (Saudi Journal of Medicine and Medical Sciences, 2024)
Background: Identifying and targeting common preventable causes of 30-day hospital readmissions could help improve survival rates and reduce the healthcare burden.